Glycogen synthase kinase 3β (GSK3β) regulates differentiation and proliferation in neural stem cells from the rat subventricular zone - Maurer, Martin H.; Brömme, Jens O.; Feldmann, Robert Enrico; Järve, Anne; Sabouri Khameneh, Fatemeh; Bürgers, Heinrich; Schelshorn, Dominik W.; Krüger, Carola; Schneider, Armin; Kuschinsky, Wolfgang (Journal of proteome research, 2007)
On the basis of its inhibition by SB216763, we identified the multifunctional enzyme Glycogen Synthase Kinase 3β (GSK3β) as a central regulator for differentiation and cell survival of adult neural stem cells. Detected by proteomic approaches, members of the Wnt/β-catenin signaling pathway appear to participate in enhanced neuronal differentiation and activated transcription of β-catenin target genes during GSK3β inhibition, associated with decreased apoptosis. Keywords: Neural stem cell • Neurosphere • Glycogen Synthase Kinase 3β • Two-dimensional gel electrophoresis • Rat • Subventricular zone
Gesehen am 30.04.2021